Zemeljski plazovi v Sloveniji - Komac, Blaž (Georitem, 2008)
The book brings a thorough review of landslide susceptibility in Slovenia. In the introductory chapter the most significant geographical and other Slovenian literature on slope processes is listed, and then the basic characteristics of landslides are explained. The landslide susceptibility in Slovenia is presented on the example of twelve large landslides, followed by the chapter on legislation on natural disasters in Slovenia.The most important part of the book is the detailed description of methods for elaboration landslide susceptibility maps with different methods. The deterministic, statistical and probabilistic methods and corresponding maps are described into detail. Such maps have been elaborated with the geographical information system using the digital elevation model 25 x 25 m. Landslide susceptibility is finally presented in the framework of the regionalization of Slovenia that had been elaborated by the Anton Melik Geographical Institute SRC SASA and for all Slovenian municipalities. The last chapter of the book is important for geomorphology, describing the role of the landslides for the formation of relief.The book is intended to be used in spatial planning, physical geography, geography of natural hazards and other branches of geography as well as in related sciences.